2011
DOI: 10.1007/s10067-011-1808-0
|View full text |Cite
|
Sign up to set email alerts
|

Color duplex ultrasonography of temporal arteries: role in diagnosis and follow-up of suspected cases of temporal arteritis

Abstract: The objectives of this study are to study the diagnostic value of color duplex ultrasonography (CDU) compared with the clinical results and temporal artery biopsy (TAB) in patients with suspected temporal arteritis (TA) and evaluate the prognostic value of CDU in follow-up of patients of sure diagnosis of TA under treatment in correlation to clinical response. The study included 32 consecutive patients of clinically suspected TA, and 30 age- and gender-matched control subjects. Baseline clinical characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 17 publications
0
34
0
3
Order By: Relevance
“…Salvarani et al reported that only halos >1 mm in thickness increased the probability of positive result of TA 20. On the contrary, Habib et al showed that smaller halos of ≥0.5 mm thickness can predict TA, a finding reported by others 7,21,22. In addition, bilateral halo sign yields a sensitivity of 37% and specificity of 100% in the diagnosis of TA, suggesting that the presence of bilateral halo sign in patients with clinically suspected TA can replace TAB in their final diagnosis, a suggestion reported by other studies 7,20.…”
Section: Discussionmentioning
confidence: 94%
“…Salvarani et al reported that only halos >1 mm in thickness increased the probability of positive result of TA 20. On the contrary, Habib et al showed that smaller halos of ≥0.5 mm thickness can predict TA, a finding reported by others 7,21,22. In addition, bilateral halo sign yields a sensitivity of 37% and specificity of 100% in the diagnosis of TA, suggesting that the presence of bilateral halo sign in patients with clinically suspected TA can replace TAB in their final diagnosis, a suggestion reported by other studies 7,20.…”
Section: Discussionmentioning
confidence: 94%
“…In one study, the presence of a halo sign on color Doppler ultrasound yielded 81% sensitivity and 88% specificity, whereas the presence of a bilateral halo sign was 37% sensitive and 100% specific. 113 In a 72-year-old woman with biopsy-proven GCA, Chaigne et al 114 reported CT and PET scan findings that showed aortic wall thickening and increased metabolic uptake without clinical involvement of the temporal arteries. Because PET does not image the temporal artery well, this type of imaging can be helpful for identifying larger vessel involvement in the unusual or atypical presentation of GCA.…”
Section: Giant Cell Arteritismentioning
confidence: 98%
“…The most recent data show that the "halo sign" on duplex ultrasound image is highly specific for GCA (81% for unilateral halo and 100% for bilateral halo), and therefore biopsy adds nothing to the evaluation in these cases. 12,19 In fact, it would be difficult to imagine the justification not to treat a patient with an abnormal duplex ultrasound result, regardless of biopsy result, given biopsy's high falsenegative rate. With greater limitation of surgical resources, it becomes difficult to defend continuing to perform invasive procedures such as biopsy if the result will not influence the treatment decision.…”
Section: Original Research and Contributionsmentioning
confidence: 99%